The Covid-19’s Impact on Sharia banks in Southeast Asia: Islamicity Performance Index, Intellectual Capital, and Islamic Corporate Governance - Abadi, M. Kurnia Rahman; Mohd Nasarudin, Ahmad Fawwaz Bin; Alhamdamuhar, Abdul Thoriq (Integrated Journal of Business and Economics (IJBE), 2025)
The COVID-19 pandemic has impacted Islamic banking in Southeast Asia, with corporate governance playing a crucial part in handling and controlling companies. This research studies the influence of issues such as Intellectual Capital, Islamic Income vs. Non- Islamic Income Ratio, and Zakat Performance Ratio on Islamic Corporate Governance in the region post-pandemic. The present research employs quantitative research techniques that depend on secondary data. To gather the necessary data, a documentation approach was adopted, involving the examination of annual reports from Islamic banks in Southeast Asia. Data was acquired through the utilization of a panel data regression model operated by Eviews 12. Findings suggest that intellectual capital and the Islamicity performance index are key drivers of ICG. To improve governance, Islamic banking institutions should focus on preserving intellectual capital and enhancing their Islamicity performance. Continuous efforts to enhance ICG are critical for dealing with global concerns in the aftermath of COVID-19.